Identifying turbulent spots in transitional boundary layers - Rehill, Brendan; Walsh, Ed J.; Schlatter, Philipp; Brandt, Luca; Zaki, Tamer A.; McEligot, Donald M. (Proceedings of the ASME Turbo Expo, 2011)
An artificial turbulent spot is simulated in a zero free-stream turbulence base flow and a base flow with organised streaks. Six identification methods are used in order to isolate the turbulent spot from the surrounding non-turbulent fluid. These are (i) instantaneous wall-normal velocity, v′, (ii) instantaneous spanwise velocity, w′, (iii) instantaneous turbulent dissipation, (iv) λ2 - criterion, (v) Q - criterion and (vi) gradient of the Finite Time Lyapunov Exponent. All methods are effective in isolating the turbulent spot from the streaks. The robustness of each technique is determined from the sensitivity of the maximum spot dimensions to changes in threshold level. The Q-criterion shows the least sensitivity for the zero free-stream turbulence case and the instantaneous turbulent dissipation technique is least sensitive in the organised streaks case. For both cases the v′ technique was the most sensitive to changes in threshold level. Copyright © 2011 by ASME.
CRIS-Team Scopus Importer:2023-03-21